Engineering Heart Valve Interfaces Using Melt Electrowriting: Biomimetic Design Strategies from Multi‐Modal Imaging. Issue 24 (30th November 2022) - Vernon, Michael J.; Lu, Jason; Padman, Benjamin; Lamb, Christopher; Kent, Ross; Mela, Petra; Doyle, Barry; Ihdayhid, Abdul Rahman; Jansen, Shirley; Dilley, Rodney J.; De‐Juan‐Pardo, Elena M.
Abstract: Interfaces within biological tissues not only connect different regions but also contribute to the overall functionality of the tissue. This is especially true in the case of the aortic heart valve. Here, melt electrowriting (MEW) is used to engineer complex, user‐defined, interfaces for heart valve scaffolds. First, a multi‐modal imaging investigation into the interfacial regions of the valve reveals differences in collagen orientation, density, and recruitment in previously unexplored regions including the commissure and inter‐leaflet triangle. Overlapping, suturing, and continuous printing methods for interfacing MEW scaffolds are then investigated for their morphological, tensile, and flexural properties, demonstrating the superior performance of continuous interfaces. G‐codes for MEW scaffolds with complex interfaces are designed and generated using a novel software and graphical user interface. Finally, a singular MEW scaffold for the interfacial region of the aortic heart valve is presented incorporating continuous interfaces, gradient porosities, variable layer numbers across regions, and tailored fiber orientations inspired by the collagen distribution and orientation from the multi‐modal imaging study. The scaffold exhibits similar yield strain, hysteresis, and relaxation behavior to porcine heart valves. This work demonstrates the ability of a bioinspired approach for MEW scaffold design to address the functional complexity of biological tissues. Abstract : Multi‐modal imaging techniques unravel the orientation of collagen fibers connecting different regions of the aortic heart valve, which is used to inspire novel design methods for melt electrowritten scaffolds. Biomimetic scaffolds exhibit continuous interfaces, gradient porosities, region‐specific layer numbers, and tailored fiber orientations in a singular design. Mechanical testing shows native tissue‐like behavior, including yield strain, hysteresis, and stress relaxation.